Saponin-enriched sea cucumber extracts exhibit an antiobesity effect through inhibition of pancreatic lipase activity and upregulation of LXR-β signaling. (2nd August 2016) - Guo, Lu; Gao, Ziyang; Zhang, Liuqiang; Guo, Fujiang; Chen, Yan; Li, Yiming; Huang, Cheng
Abstract: Context : Sea cucumbers have been consumed as tonic, food, and nutrition supplements for many years. Objective : The objective of this study is to investigate the antiobesity and lipid-lowering effects of sea cucumber extracts in in vitro and in vivo models and elucidate the mechanism of action of the extracts on obesity and dyslipidemia. Materials and methods : The 60% ethanol extracts from the body walls of 10 different sea cucumbers were investigated for the inhibition of pancreatic lipase (PL) activity in vitro . The optimal active extract (SC-3) was further chemically analyzed by LC-MS and UV. And 0.1% and 0.2% of SC-3 was mixed with a high-fat diet to treat C57/BL6 mice for 6 weeks or 2 weeks as preventive and therapeutic study. The body weight, serum, and liver lipid profile in the mice were investigated. Results : The crude extract of Pearsonothuria graeffei Semper (Holothuriidae) inhibited the PL activity by 36.44% of control at 0.5 μg/mL. SC-3 and echinoside A inhibited PL with an IC50 value at 2.86 μg/mL and 0.76 μM. 0.1% of SC-3 reduced the body weight (23.0 ± 0.62 versus 26.3 ± 0.76 g), the serum TC (2.46 ± 0.04 versus 2.83 ± 0.12 mmol/L), TG (0.19 ± 0.08 versus 0.40 ± 0.03 mmo/L), and LDL-c (0.48 ± 0.02 versus 0.51 ± 0.02 mmol/L), and liver TC (1.19 ± 0.17 versus 1.85 ± 0.13 mmol/mg) and TG (6.18 ± 0.92 versus 10.87 ± 0.97 mmol/mg) contents of the obese C57BL/six mice on a high-fat diet. Discussion and conclusion : Sea cucumber may be used for developing antiobesity and antihyperlipidemia drugs.